Communication Patterns of Meaning in the Melancholic Character of Gundala: A Semiotic Analysis of Charles Sanders Peirce - Jaqualine Pramanta Putra; Fauzi Syarief; Mursyid Kasmir; Susana Susana (Sean Institute, 2026)
This study aims to analyze how the construction of melancholic character meaning is represented in the film Gundala directed by Joko Anwar through the semiotic approach of Charles Sanders Peirce. The focus of this research is directed toward identifying visual and verbal signs that represent the melancholic characteristics of the main character, as well as interpreting the meanings embedded within those signs. This study employs a qualitative descriptive method using Peirce’s semiotic analysis framework, which consists of three categories: icon, index, and symbol. The data were collected through film observation and in-depth interviews with the director. The findings reveal that the character is constructed as a melancholic figure characterized by doubt, reflectiveness, and emotional depth. This representation is developed through visual signs, such as gloomy facial expressions, dim lighting, and cool color tones, as well as verbal signs in the form of dialogues that reflect inner conflict and hesitation. Therefore, the film can be interpreted as a reflection of human psychological conditions in the midst of social and moral pressures.